PENDIDIKAN AGAMA ISLAM: KAJIAN PERSPEKTIF ONTOLOGI & AKSIOLOGI - Rosichin Mansur (ANDRAGOGI, 2021)
Islamic education is something that exists, a true reality, not a string of words or images that will be lost in the dark. Islamic education as an activity that can be known to humans through its effects in life. Likewise, Islamic education is a means that has a good relationship with humans, nature and God. Islamic education is an education that carries a myriad of values given to humans. The values carried by Islamic education such as divine values, human values, absolute values, relative values, objective values and subjective values as well as usefulness values in life.Keywords: Islamic education, ontology, axiologyAbstrakPendidikan Islam merupakan sesuatu ‘yang ada’, sebuah realitas yang benar adanya, bukan suatu deretan kata atau bayangan yang akan hilang dalam kegelapan. Pendidikan Islam sebagai suatu aktifitas yang dapat diketahui manusia melalui pengaruh-pengaruhnya dalam kehidupan. Demikian pula pendidikan Islam sebuah sarana yang memiliki hubungan baik dengan manusia, alam dan Tuhan. Pendidikan Islam merupakan pendidikan yang mengusung segudang nilai yang diberikan pada manusia. Nilai-nilai yang diusung pendidikan Islam seperti nilai ketuhanan, nilai kemanusiaan, nilai absolut, nilai relatif, nilai obyektif dan nilai subyektif serta nilai kegunaan dalam kehidupan.Kata Kunci: pendidikan Islam, ontologi, aksiologi